The influence of CHSE (Cleanliness, Health, Safety, Environmental Sustainability) and Attributes of Tourism Products on Tourist Satisfaction and Intention to Visit Again in Semilir Hamlet, Semarang Regency, Central Java - Mahendra Jati, Ronald (Asian Journal of Social and Humanities, 2023)
The Influence of CHSE Implementation and Tourism Product Attributes in Dusun Semilir in the Post-COVID Era, to Determine Tourists' Perceptions of the Impact of CHSE Implementation and Tourism Product Attributes on Satisfaction and Intention to Revisit Tourists, in order to align the development of tourism in Semilir Hamlet with tourists' needs. The aim of this research is to understand the influence of CHSE and tourism attributes on tourists' intention to revisit through tourist satisfaction. The method used is quantitative with a descriptive approach. The number of respondents used is 100 respondents. The data analysis used is SEM-PLS. The results show that tourism attributes do not have a significant influence on tourists' intention to revisit, but CHSE significantly influences tourists' intention to revisit. With tourist satisfaction, tourism attributes have their influence on the intention to revisit, and CHSE through tourist satisfaction has its influence on tourists' intention to revisit Dusun Semilir. These results indicate that satisfaction plays a significant role in the influence of CHSE and tourism attributes on tourists' intention to revisit